THE ALLUREMENT OF COUNTERFEIT PURCHASE BEHAVIOR: A CASE STUDY AMONG YOUTH CONSUMERS OF MALAYSIA - Nurazreen Zulkeply; Azlia Jaapar; Noorsyahira Musa; Nur Hafizah Hidayat; Rosita Husain (International Journal of Accounting, Finance and Business, 2021)
Counterfeiting products are low-quality imitations of original products or fakeluxury items. Producing and buying counterfeiting products are considered as the crime of the21st century because its affect the luxury branded market. Lately, the rapid demand for thesecounterfeiting products caused the luxury branded market sufferer for losses, which strives fora low distribution to keep the demand high. Therefore, the purpose of this study is to determinethe core factors on youth’s purchase behaviors towards counterfeit goods. The study also setout three common factors to examine the relationship of consumers’ buying behavior towardscounterfeit products. The primary data were used, which was collected through questionnairesconsisting of 27 questions. A survey of 200 respondents was conducted in Klang Valley.Correlation and regression analysis were used. The results of the study show that there ispositive impact between past purchase experience on purchasing behavior of counterfeitingproducts. Thus, the experience of purchasing counterfeiting products is the core factors onpurchasing of these products. By having a better understanding of the consumers’ purchasingbehavior of buying counterfeit products of the genuine brand products can make bettermarketing strategies.